DESIGN AND OPTIMIZATION OF VCO AND OLEIC ACID FOR NLC QUERCETIN USING SIMPLE LATTICE DESIGN - Cahyono, Definta Anisa Tamara; Rosita, Noorma; Erawati, Tristiana (Medical Sains : Jurnal Ilmiah Kefarmasian, 2025)
Quercetin is a flavonoid compound that exhibits skin-brightening activity by inhibiting tyrosinase. However, its topical application is limited because of its low solubility. A Nanostructured Lipid Carrier (NLC) was selected as the delivery system to enhance the stability and topical efficacy of quercetin. This study aimed to optimize the combination ratio of oleic acid and Virgin Coconut Oil (VCO) as the liquid lipid phase in the NLC Blank Formulation using the Simplex Lattice Design (SLD) method. Eight blank NLC formulations were prepared using the high-shear homogenization method and were evaluated based on organoleptic properties, particle size, polydispersity index (PDI), pH, and real-time stability over 30 days. Eight blank NLC Blank Formulations showed that a balanced VCO to oleic acid ratio (5.5:4.5) produced small particle sizes (<160 nm), low polydispersity index (PDI <0.25), and good physical stability. Blank Formulations dominated by either VCO or oleic acid tended to have larger particles and lower stability, indicating that the liquid lipid ratio influenced the NLC characteristics. Optimization using the Simplex Lattice Design (SLD) method identified three optimal lipid ratios: B1 (4.86:5.31), B2 (2:8), and B3 (9:1), each with desirability values near 1. The model was validated by comparing the predicted (dry lab) and experimental (wet lab) data, which showed no significant differences in key parameters (p > 0.05), confirming the reliability of the SLD model. This approach effectively optimized quercetin-loaded NLC Blank Formulations, and the three selected Blank Formulas serve as a strong basis for developing topical quercetin NLC products.